Pengaruh Viral Marketing Terhadap Kepercayaan Konsumen dan Dampaknya Pada Keputusan Pembelian Produk Ms Glow - Suhaemi Suhaemi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The study aims to determine the influence viral marketing on purchasing decisions with consumer trust as an intervening variable on MS Glow. This type of research is quantitative and uses descriptive analysis method. The data analysis technique used is path analysis. The sample used in this study amounted to 98 respondents who knew the social media instagram MS Glow, and once bought and consumed MS Glow by using purposive sampling. In this study using data collection techniques with questionnaires and analyzed using path analysis. The conclusion of this study is (1) the Viral Marketing have a significant effect on Consumer Trust with a value of 10,890 , (2) the Viral Marketing have a significant effect on Purchasing Decisions with a value of 8,137, (3) Consumer Trust have a significant effect on Purchasing Decisions with a value of 3,555, and (4) consumer trust is not able to mediate viral marketing on purchasing decisions with a Z value of 1,389.